Risks related to drug use among male construction workers - Aroldo Gavioli; Thais Aidar de Freitas Mathias; Robson Marcelo Rossi; Magda Lúcia Félix de Oliveira (Escola Paulista de Enfermagem, Universidade Federal de São Paulo, 2014)
Objective To identify the prevalence of risk related to drug use among workers of a construction company and to evaluate how it relates with sociodemographic variables. Methods A cross-sectional study conducted with 418 workers who were given the Alcohol, Smoking and Substance Involvement Screening Test. Multinominal logistic regression was used as a measure of association. Results Tobacco, alcohol, cannabis, cocaine and inhalants were the most used drugs. Moderate and high risks were related, respectively, to the use of tobacco (32.5% and 5.7%), alcohol (26.8% and 6.9%), cannabis (2.6% and 2.4%) and cocaine (1.2% and 0.5%). Conclusion Tobacco and alcohol were the main drugs used by workers. The level of risk related to the use of tobacco, alcohol, cannabis and cocaine were high when compared to that of the general population.